Outcome of Patients in Term of Range of Motion after Total Knee Arthroplasty with all Poly Implants - Fraz Noor, Kamran Saeed, Agha Momin, Naeem Mehmood Mughal, Zulfiqar Ali Soomro, Mehtab Ali Shahani (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the outcome of patients in term of range of motion after total knee arthroplasty with all poly implants. Study Design: Retrospective study Place and Duration of Study: Department of Orthopaedics, Sahara Medical College, Narowal from 1st April 2021 to 31st March 2022. Methodology: Sixty various patients who came for total knee arthroplasty were selected on the basis of their conditions. Patients were divided into two inserts groups for understanding the better outcome results in terms of range of motion (ROM). Thirty patients having fixed bearing and other 30 patients having mobile bearing inserts will all poly implants. A standardized medial-parapatellar approach was taken for surgical procedure and resection of primary tibia was done. Pain function and evaluation was performed through knee society scoring (KSS) as well as VAS score and goniometer was used for analyzing range of motion which was defined as degree of flexion of knee subtracting from number of extension-defect. Results: There was no significant difference in either the gender or ages of both implants selected patients However the mobile bearing group patients has a better BMI value than the fixed bearing implant patients. In term of range of motion mobile bearing group patients had a higher ROM value than the fixed bearing operated patients in case of overall change in range of motion analysis. The Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index, score showed a significant change with an increased value observed in mobile bearing implant patients. Conclusion: Visual analogue pain score show significant difference in mobile and fixed bearing group. In terms of range of motion, mobile implants show better outcome in contrast to fixed bearing group. Keywords: Knee implants, Mobile, Fixed bearing, Outcomes, Osteolysis